Teaching materials for English in the primary education – also for the pre-school education? - Olpińska-Szkiełko, Magdalena (Glottodidactica, 2015)
The objective of the article is to analyse some selected materials for teaching English as a foreign language, designed mainly for grade 1–3 of the primary school, with the goal to answer the question whether these materials could be also used successfully and efficiently with 3–5-year old children. Early English learning materials are compared with Polish integrated learning materials. The analysis results in some conclusions for the didactic process in kindergartens. In accordance with the theoretical issues some principles for the shaping of didactic materials, teaching forms and activities, adequate tasks and contents of a language lesson are described.